Analisis Kemampuan Penggunaan Ajektiva Dalam Pembentukan Kalimat Bahasa Prancis - Reyvano, Aghna; Karimah, Iim Siti; Racmadhany, Ariessa (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
The mastery of adjectives in French is a crucial aspect of forming grammatical and meaningful sentences. However, learners of French as a foreign language often experience difficulties, particularly in gender and number agreement as well as adjective placement. This study aims to analyze the level of mastery of French adjectives and to identify the types of difficulties and factors contributing to errors among A2-level students in the French Language Education Program at Universitas Pendidikan Indonesia. This study employs a sequential explanatory mixed-method design, integrating quantitative and qualitative data. Quantitative data were obtained through an 82-item paper-based written test, while qualitative data were collected through open- and closed-ended questionnaire items. All data were analyzed descriptively based on the framework of French adjective grammar proposed by Grevisse (2008). The findings indicate that most students achieved a good level of proficiency, with an average score of 76, and demonstrated an understanding of basic adjective functions. Nevertheless, frequent errors were found in gender and number agreement, adjective placement, and particularly in the use of l’adjectif indéfini, which showed the highest error rate. These results suggest the need for instructional practices that emphasize explicit explanations of adjective agreement and placement, accompanied by contextualized exercises specifically targeting the mastery of l’adjectif indéfini.